2018
DOI: 10.1080/17451000.2018.1472383
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, relative growth and morphological sexual maturity of the snapping shrimp Alpheus brasileiro Anker, 2012 (Caridea: Alpheidae) from the south-eastern coast of Brazil

Abstract: The present study investigated the population structure of the snapping shrimp Alpheus brasileiro. We tested the hypotheses that the sex ratio of the population differs from the expected 1:1 and that the growth pattern differs between adults and juveniles and between sexes. Reproductive period, juvenile recruitment and morphological sexual maturity were estimated. Samples were collected in two periods. The first sampling occurred bimonthly from March 2013 to January 2014. The second sampling occurred monthly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Our results regarding the growth parameters and longevity are consistent with the estimates of the morphological sexual maturity obtained through the use of the relative growth method (Pescinelli et al, 2018a). With this method it was estimated that males reach the sexual maturity at a slightly larger size (4.9 mm CL) than the females (4.7 mm CL).…”
Section: Growth Longevity and Mortality Of Alpheus Brasileirosupporting
confidence: 88%
See 3 more Smart Citations
“…Our results regarding the growth parameters and longevity are consistent with the estimates of the morphological sexual maturity obtained through the use of the relative growth method (Pescinelli et al, 2018a). With this method it was estimated that males reach the sexual maturity at a slightly larger size (4.9 mm CL) than the females (4.7 mm CL).…”
Section: Growth Longevity and Mortality Of Alpheus Brasileirosupporting
confidence: 88%
“…Previous studies investigated the biology of A. brasileiro analyzing egg production and social monogamy (Pescinelli et al, 2017a), relative growth (Pescinelli et al, 2018a) and showed that males and females have different relative growth, and that reproduction and recruitment are continuous. The morphology of early larval stages was also analyzed, and led to the conclusion that A. brasileiro has an extended larval development in the plankton (Pescinelli et al, 2017b).…”
Section: Growth Longevity and Mortality Of Alpheus Brasileiromentioning
confidence: 99%
See 2 more Smart Citations
“…Heterochely, here defined as different-sized chelipeds, is a common attribute in most decapods (e.g. Aegla franca Schmitt, 1942: Bueno andShimizu 2009;Alpheus brasileiro Anker, 2012: Pescinelli et al 2018Platyxanthus crenulatus [Milne-Edwards, 1879]: Laitano et al 2013), including members of the family Callianassidae Dana, 1852 (collectively known as ghost shrimps). Adult males of callianassids invariably develop one hypertrophied cheliped (heterochely), while females and juveniles have subequal or homochelous chelipeds (Hernáez 2018 and references therein).…”
Section: Introductionmentioning
confidence: 99%